2020
DOI: 10.3390/ijerph17239006
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Its Associated Factors among Patients with Dementia

Abstract: Constipation is one of the most frequent non-motor problems in older adults. As constipation is commonly ignored by dementia patients, it is not usually reported on time. Constipation has a serious impact on the activity of daily living and quality of life in dementia patients. The relationships between constipation, demographic variables, and the nutritional status of patients with dementia remain unknown. This study aimed to assess the possible factors associated with constipation. This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…The specific pathogeneses of constipation and dementia are still unclear, but an increasing number of studies has shown that there is an important connection between them ( Idiaquez and Roman, 2011 ; Chen et al, 2020 ; Leta et al, 2021 ). The gut is connected to the brain through the gut-brain axis ( Rhee et al, 2009 ); that is, the central nervous system communicates with the enteric nervous system, intestinal mucosa and muscle layer through two-sided (afferent and efferent) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The specific pathogeneses of constipation and dementia are still unclear, but an increasing number of studies has shown that there is an important connection between them ( Idiaquez and Roman, 2011 ; Chen et al, 2020 ; Leta et al, 2021 ). The gut is connected to the brain through the gut-brain axis ( Rhee et al, 2009 ); that is, the central nervous system communicates with the enteric nervous system, intestinal mucosa and muscle layer through two-sided (afferent and efferent) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore need to confirm our findings in a larger study. However, previous studies have reported that the prevalence rate of constipation was 15%–20% in a population over 60 years old and 25% in patients over 70 years old 13 . In this study, the prevalence rate of constipation was 23.8%, which suggests that our cases could partially represent patients of interest.…”
Section: Discussionmentioning
confidence: 47%
“…Constipation is frequently observed even in healthy adults, and its prevalence rate increases in the elderly 1,2 . Moreover, constipation can be a risk of neurodegenerative diseases, such as Parkinson's disease (PD) and Dementia with Lewy body (DLB), 23,24 while association of constipation with AD pathology is controversial 13 . Recently, the association between constipation and the gut microbiome has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Тяжесть запора положительно коррелирует с наличием и выраженностью когнитивных расстройств [44]. Пациенты с деменцией часто не предъявляют жалобы на наличие симптомов запора и вместо этого могут демонстрировать агрессивное поведение, что приводит к назначению антипсихотических препаратов и, как следствие, усугублению симптомов запора [45,46].…”
Section: клиническая картинаunclassified